2017
DOI: 10.1002/dta.2226
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of drug products received for analysis in the Swedish STRIDA project on new psychoactive substances

Abstract: The web-based open sale of unregulated new psychoactive substances (NPS) has shown a steady increase in recent years. Analysis of drug products sold as NPS is useful to confirm the true chemical contents, for comparison with the substances detected in corresponding body fluids, but also to study drug trends. This work describes the examination of 251 drug products that were randomly submitted for analysis in 173 cases of suspected NPS-related intoxications in the Swedish STRIDA project in 2010-2015. Of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…It is noteworthy that Brunt et al () showed by analyzing test purchases that several products were mislabeled. However, Backberg, Jonsson, Beck, and Helander () showed that there was a high degree of consistency (88%) between suspected and actual content in investigated drug products. Nevertheless, the content of branded products may be subject to variations.…”
Section: Demands On Scientific Case Reportsmentioning
confidence: 99%
“…It is noteworthy that Brunt et al () showed by analyzing test purchases that several products were mislabeled. However, Backberg, Jonsson, Beck, and Helander () showed that there was a high degree of consistency (88%) between suspected and actual content in investigated drug products. Nevertheless, the content of branded products may be subject to variations.…”
Section: Demands On Scientific Case Reportsmentioning
confidence: 99%
“…This is likely due to their increased availability through a more Internet-connected society, 6 diverse domestic narcotic legislation, and a low risk for the abuser to be caught in standard urine drug tests. [8][9][10][11] A wide range of adverse side effects have also been observed with intoxications, ranging from cardiovascular and neurological to psychiatric effects, like tachycardia, arterial hypertension, hallucinations, aggressiveness, agitation, hyperthermia, and locomotor behavior alterations. Intoxications and deaths associated with the use of these substances have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…32,53,54 The retention times of the investigated compounds with the methylenedioxy motif (compounds[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] were in the range of2.2-3.4 minutes when using the fast GC-MS screening method applied at the NFC (Figure S39). In this work, the hyphenated methods GC-MS and GC-FTIR were applied.…”
mentioning
confidence: 99%
See 2 more Smart Citations